Molecular signatures diversity unveiled through a comparative transcriptome analysis of longissimus dorsi and psoas major muscles in Hanwoo cattle - Sunirmal Sheet; Sun Sik Jang; Jin-A. Lim; Woncheoul Park; Dahye Kim (Animal Biotechnology)
This study investigates the transcriptome-level alterations that influence production traits and early fattening stage myogenesis in Hanwoo cattle, specifically focusing on the highly prized Longissimus dorsi (LD) and Psoas major (PM) skeletal muscles, which hold significant commercial value. We conducted RNA sequencing analysis on LD and PM muscles from 14 Hanwoo steers (n = 7, each group) at the age of 10 months, all fed the same diet. Our results unveiled a total of 374 and 206 up-regulated differentially expressed genes (DEGs) in LD and PM muscles, respectively, with statistical significance (p < 0.05) and a log2fold change ≥ 1. Genes governing muscle development processes, such as PAX3, MYL3, COL11A1, and MYL6B, were found to be expressed at higher levels in both tissues. Conversely, genes regulating lipid metabolism, including FABP3, FABP4, LEP, ADIPOQ, and PLIN1, exhibited higher expression in the PM muscle. Functional enrichment analysis revealed a tissue-specific response, as PM muscle showed increased lipid metabolism allied pathways, including the PPAR signaling pathway and regulation of lipolysis in adipocytes, while LD was characterized by growth and proliferative processes. Our findings validate the presence of a muscle-dependent transcription and co-expression pattern that elucidates the transcriptional landscape of bovine skeletal muscle.